Ballet Shoes - Streatfeild, Noel; Floethe, Richard (New York Dell Pub. Co., 1979)
Relates the fortunes of three adopted sisters who take dancing and stage training, one to become an actress, the second a ballerina, and the third an aviatrix.
"A Yearling Book."
Reprint of the ed. published by Random House.
75595
Keywords: Acting -- Vocational guidance -- Juvenile fiction; Ballet -- Juvenile fiction